Ethnomathematics: Ideofacts, Sociofacts, and Artefacts of Mathematical Context in Yogyakarta - Sugiman, Sugiman; Fauzan, Ahmad; Maulyda, Mohammad Archi; Johar, Rahmah; Anwar, Lathiful (Journal of Education Culture and Society, 2025)
Aim. The purpose of this study is to explore ideofacts, sociofacts, and artifacts that have the potential to serve as contexts for teaching mathematics in Yogyakarta.Methods. This qualitative research employs an ethnographic approach. The study investigates potential locations including the Kotagedhe Mataram Mosque, Prambanan Temple, and the Planting Plantation System in Yogyakarta. Instruments used include interview guides, observation sheets, and artifact exploration Tables. Key informants were selected at each research site to provide ethical insights from an emic perspective, resulting in dialectical data. To ensure data validity, the researchers sutilised data triangulation (interviews, observations, and documentation) and conducted focus group discussions (FGDs) with cultural experts and ethnomathematicians to review and discuss the findings.Results. The findings indicate that each location contains mathematical content applicable to teaching, particularly in geometry (both two-dimensional and three-dimensional), pre-algebra (multiplication), and number theory (least common multiple).Conclusion. The study demonstrates how cultural contexts, such as the Kotagedhe Mataram Mosque and Prambanan Temple, can be integrated into elementary mathematics education, illustrating mathematical concepts such as spatial geometry, symmetry, and multiplication. It identifies potential learning tools, including folded paper, flat-shaped paper, LEGO, and Augmented Reality, to enhance the teaching of these concepts. Additionally, a Hypothetical Learning Trajectory (HLT) is developed to guide the learning process based on these cultural contexts and tools.